Wellness and illness: the aftermath of urban mass housing in Lagos, Nigeria. Issue 7 (3rd October 2018) - Kasim, Oluwasinaayomi Faith
ABSTRACT: Mass housing policy and an attendant population increase play a vital role in the socio-economic profile of Lagos. The article, using data from mass housing projects, explains the effects of these projects on intra-urban dynamics and the implications in Lagos. The pace of urban growth is increasing, and there is an absence of supporting infrastructures. The areas where populations are decreasing happen to be where contemporary housing construction is concentrated. Therefore, programmes aimed at providing housing and improving quality of life should, as a priority, deal with factors affecting population growth and spatial distribution.